2017
DOI: 10.1016/j.surfcoat.2017.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser shock peening on the high temperature oxidation resistance of titanium

Abstract: a b s t r a c tThe effect of laser shock peening on the high temperature oxidation resistance of commercial pure titanium at high temperature (700°C) was studied in long-time (3000 h) exposure under dry air. A reduction of the gain mass by a factor 4 was found for laser-shock peened (LSP) samples compared to untreated titanium, which supports the interest of laser-shock treatment for the improvement of high temperature resistance. Short-durations (10 h and 100 h) oxidation experiments, devoted to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 32 publications
8
27
0
Order By: Relevance
“…As it was reported in previous works [11,12], in the case of commercially pure Ti-a untreated and SP treated samples studied in the same conditions showed spallation of the oxide layer after about 1700 h at 7000 °C. On the contrary, LSP treated Ti-a showed a homogeneous oxide layer, and a mass gain of 6.7 mg/cm 2 after 3000 h.…”
Section: Long-duration Ht Oxidation Experimentssupporting
confidence: 82%
See 1 more Smart Citation
“…As it was reported in previous works [11,12], in the case of commercially pure Ti-a untreated and SP treated samples studied in the same conditions showed spallation of the oxide layer after about 1700 h at 7000 °C. On the contrary, LSP treated Ti-a showed a homogeneous oxide layer, and a mass gain of 6.7 mg/cm 2 after 3000 h.…”
Section: Long-duration Ht Oxidation Experimentssupporting
confidence: 82%
“…Recent works by Raceanu et al [9] show a positive role of the mechanical treatments in the oxidation resistance of zirconium due to the large compressive stresses induced by the treatment underneath the surface. More recently, Kanjer et al reported the beneficial effect of mechanical treatments on the oxidation resistance of pure titanium at high temperature in air [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the SP treatment induces contamination with WC particles coming from the shotpeening balls (14), whereas the LSP treatment preserves the surface chemically clean (15). Figure 2 shows the mass gain for long oxidation tests, up to 3000 hours.…”
Section: Characterizations Before High Temperature Oxidationmentioning
confidence: 97%
“…Two kinds of mechanical treatments were used in this work: ultrasonic shot-peening (SP) and laser-shock peening (LSP). Experimental details on both kinds of treatments are given in previous papers (14) (15). For simplicity, shot-peened samples are named here SP, while laser-shock peened samples are named LSP in the following sections.…”
Section: Materials and Mechanical Treatmentsmentioning
confidence: 99%
“…Meanwhile, only a few reports have been found on the oxidation behavior of Ti at temperatures of 700 • C and 800 • C [ [14][15][16]. There has been limited attention on the cyclic oxidation and hardness characteristics of thermally exposed Ti at elevated temperatures prepared by the inductive sintering method.…”
Section: Introductionmentioning
confidence: 99%